The shadow world inside the global arms trade - Feinstein, Andrew (London Penguin, 2012)
Andrew Feinstein, former member of the African National Congress, investigates the secretive world of the global arms trade in his gripping new book The Shadow World.
Includes bibliographical references (p. [537]-641) and index.
Keywords: Arms transfers